Bangkok Inner Orchard’s Landscape: The Interpretation from Old Maps and Photographs - Davivongs , Vudipong; Arifwidodo, Sigit (NAJUA: History of Architecture and Thai Architecture, 2020)
Bangkok Inner Orchard was a cultural landscape of fruit orchard dating back to Ayutthaya period. Thai literature and foreigners' records described the atmosphere and landscape of Bangkok Inner Orchard, regarding it as the place for premium fruit produces. However, such description lacks spatial attributes such as location and area, including landscape character and vegetation. Therefore, this study focused on interpreting old maps and photographs to fulfil the literature's missing spatial qualities. Thirteen old maps and two collections of old photographs in different periods were analysed as the empirical evidence for interpreting the embedded contents and details related to the orchard. Documents and history literature review was also used for cross-examining. The interpretation revealed a more precise understanding of Bangkok Inner Orchard's location and area, located along the Chao Phraya riverbank, mostly on the western bank of the river. Analysis of maps in 1959 and 2000 revealed the expansion of orchard areas. For landscape character issues, the old maps showed the orchard’s compartmentalised pattern called “Khanat” along with the ditches and dikes irrigation system. The inscription on the old maps and the old photographs taken on the sites helped identify vegetation types in the orchards, such as various fruit trees planted together with betel nut, coconut, and sugar palm trees. The urbanisation of Bangkok affected the changes in the inner orchard. Although the new orchard area has increased, some of the older orchards have been encroached upon by urban sprawl. Thus, they become fragmented and particularly vulnerable from the effects of directionless urbanisation.